PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS6 MATERI PERSAMAAN DAN PERTIDAKSAMAAN NILAI MUTLAK LINEAR SATU VARIABEL SMA - Dara Asri Maulani; Yuni Katminingsih; Lina Rihatul Hima (UPT Penerbitan Universitas Jember, 2022)
Based on the background of the researchers on the results of field observations, the lack of active learning in the classroom resulted in students feeling they did not understand the learning material. This is because teachers still implement learning with lectures that do not use android-based learning media. For this reason, Android-based technology using Adobe Flash CS6 was developed so that students become active in learning, making it easier for students to understand learning material. This study aimed to produce learning media based on Adobe Flash CS6 for equations and inequalities for linear absolute values ​​of one variable. This study uses the ADDIE development model, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Validation is carried out by media experts, material experts, and practitioners. The developed media was tested on 20 students of class X MIPA 6 SMA Negeri 3 Kediri. Development of learning media based on Adobe Flash CS6 in the form of the